2019
DOI: 10.1371/journal.pone.0215593
|View full text |Cite
|
Sign up to set email alerts
|

Associations of marital status with diabetes, hypertension, cardiovascular disease and all-cause mortality: A long term follow-up study

Abstract: Background To investigate the associations of marital status with major clinical outcomes including type 2 diabetes (T2D), hypertension, cardiovascular disease (CVD) and all-cause mortality. Methods The study cohort (1999–2014) included 9,737 (45% male) Iranian adults with a mean age of 47.6 years. Marital status was defined as married versus never married, divorced and widowed. The relationship between marital status and the four above mentioned outcomes were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
59
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 40 publications
21
59
8
2
Order By: Relevance
“…We found a significant and strong interaction between sex and marital status. Although marital status was not a significant risk factor for hypertension development in this study, in line with a recent study [37], we found that married men had a 17% lower and married women had a 30% higher risk of incident hypertension. It is suggested that married men have better sleep patterns and lifestyle compared to never-married men [37].…”
Section: Discussionsupporting
confidence: 91%
“…We found a significant and strong interaction between sex and marital status. Although marital status was not a significant risk factor for hypertension development in this study, in line with a recent study [37], we found that married men had a 17% lower and married women had a 30% higher risk of incident hypertension. It is suggested that married men have better sleep patterns and lifestyle compared to never-married men [37].…”
Section: Discussionsupporting
confidence: 91%
“…According to a study conducted by Birditt et al [21], this result can be explained by negative relationships in the couple leading to stress that directly affects the cardiovascular system. These findings however, contrast with those of Ramezankhani et al [22] who concluded in their study that never having been married is an important risk factor for hypertension and cardiovascular disease. The distribution of participants by type of job revealed a significant difference between groups (p < 0.001).…”
Section: Discussioncontrasting
confidence: 92%
“…This result was contradicted by the studies conducted in Iran. 21,23,24 BMI was highly associated with the risk of T2DM. The relation between BMI and risk of diabetes was demonstrated by Vaidya et al, 25 Pandya et al 26 and Gupta et al 17 Both insulin resistance and defective insulin secretion are most often seen among obese people, leading toward the occurrence of diabetes.…”
Section: Discussionmentioning
confidence: 91%